2016
DOI: 10.1364/oe.24.008149
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast second-Stokes diamond Raman laser

Abstract: This version is available at https://strathprints.strath.ac.uk/56987/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(24 reference statements)
1
10
1
Order By: Relevance
“…It can be seen from Figure 8a,b that SRS generation was observed only in a narrow range of the positive cavity length detuning from 0 up to +50 µm while the detuning range was essentially wider at the negative cavity length detuning (from 0 down to −220 µm). It is similar as in other synchronously pumped Raman lasers [65][66][67][68][69][70][71][72][73][74][75][76][77][78] and can be explained by non-efficient interaction between the pump and SRS pulses when only the leading edge of the SRS pulse is amplified at positive detuning. However, namely positive detuning (up to +50 µm) of the cavity length has allowed to obtain the strongest SRS pulse shortening, as can be seen from Figure 8c,d.…”
Section: Experimental Results Of Srs Lasingsupporting
confidence: 81%
See 1 more Smart Citation
“…It can be seen from Figure 8a,b that SRS generation was observed only in a narrow range of the positive cavity length detuning from 0 up to +50 µm while the detuning range was essentially wider at the negative cavity length detuning (from 0 down to −220 µm). It is similar as in other synchronously pumped Raman lasers [65][66][67][68][69][70][71][72][73][74][75][76][77][78] and can be explained by non-efficient interaction between the pump and SRS pulses when only the leading edge of the SRS pulse is amplified at positive detuning. However, namely positive detuning (up to +50 µm) of the cavity length has allowed to obtain the strongest SRS pulse shortening, as can be seen from Figure 8c,d.…”
Section: Experimental Results Of Srs Lasingsupporting
confidence: 81%
“…The individual pump pulses can be shorter than τ c and even ultra-short realizing transient SRS in a cavity. Such systems are synchronously pumped Raman lasers [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. If we use a train of ultra-short pulses with the pulse train duration of t p at the individual pulse duration of τ p , the extracavity synchronously pumped SRS oscillation threshold will be defined by expression (12) where τ p should be replaced with t p and p = 1 for both ring and linear cavities (at τ p < τ c we have gain only in the forward direction) but the SRS gain G (and its threshold value G th in expression (12)) is defined by τ p as before by expression (8).…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The spectra were measured using an optical spectrum analyzer (HP 86,140 A). The second-Stokes wavelength was not always exactly two Stokes shifts longer than the pump center wavelength owing to spectral broadening of the Stokes field by self-phase modulation (Murtagh et al, 2015 b ). The output power of the second-Stokes emission is shown in Figure 2b and was up to 80 mW, making the laser suitable for two-photon imaging of biological specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The laser described allows tuning of the second-Stokes emission to 1,200 nm, for a pump wavelength of 900 nm. Femtosecond (fs) diamond Raman lasers emitting first-Stokes (Murtagh et al, 2015; Lin & Spence, 2016) and, more recently, second-Stokes (Murtagh et al, 2015 b ) radiation have been demonstrated, but have, to our knowledge, not been used for imaging. Analogous synchronously pumped fiber Raman lasers have also recently been developed (Churin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies were carried out in the steady-state mode, when the pump pulse duration is longer than the dephasing time in diamond. Less work has been done on the transient mode, when the pulse duration is shorter than the dephasing time: DRLs under femtosecond (fs) pumping in synchronously-pumped cavities has been demonstrated [2], and supercontinuum (SC) generation in diamond under fs pumping has been reported [3]. The major mechanism for SC generation under fs laser pumping is believed to be self-phase modulation (SPM).…”
mentioning
confidence: 99%